Response of Preterm Infants of Mothers Who Are Chronic Carriers of Both HBsAg and HBeAg to Pre-52 Containing Hepatitis 8 Vaccine (TGP 943) - A Preliminary Report - Abdul Hamid Sutohardjo (Paediatrica Indonesiana, 1995)
This study aimed to examine the immunogenccity and protective efficacy of a pre-S2 containing hepatitis B vaccine (TGP 943, Takada, Japan) in 9 preterrn infants. A control group of preterm infants were given plasma derived hepatitis B vaccine (Korean Green Cross, Korea). All these preterm infants were born to both HBsAG and HBeAg posistive mothers and born in central General Hospital Sanglah Denpasar from January 3, 1992 to October 30, 1992. The gestational ages were 35-37 weeks and birth weights were 2000-2500 grams. The difference of the anti pre-S2 antibody between two groups of preterm infants was evident at month 6. Anti-HBs antibody response was almost same in the two groups of preterm infants. None in preterm infants in this study became positive for HBsAg during follow-up for at least 6 months. 2 of 8 preterm infants in control group become positive for HBsAg during follow up for a t least 6 months. Our study demonstrated a better anti pre-S2 antibody response and also comparable anti-Hbs antibody response in preterms infants vaccinated with a pre-S2 containing hepatitis B vaccine, compared with those with conventional plasma-derived vaccine.